Pelatihan Pengumpulan Data dan Fakta Pola Liputan Media Bagi Aparat Polres Luwu Utara - Zulkarnain Hamson; Fyan Andinasari Kuen; St. Shofiyah; Mitha Mayestika Kuen (Celebes Abdimas: Jurnal Pengabdian Kepada Masyarakat, 2020)
Abstract. The Police of the Republic of Indonesia, face problems related to the quality and service standards of their officers at all levels. The development of communication technology, also influences society, both culture and behavior. This situation has forced the police to move towards evaluating service standards and the quality of their officers. The question of how the police can approach, and provide services to the community, and adopt a pattern of media coverage in carrying out their duties, is sought to be realized through this training. With the methods of lecturing, field practice, discussion and evaluation, this training has succeeded in gaining insight and knowledge, as well as providing solutions to the problems of Bhayangkara, Community Security Guidance and Police Operators in North Luwu Regency, South Sulawesi Province.